Performance of cellulose acetate-polyethersulfone blend membrane prepared using microwave heating for palm oil mill effluent treatment - Idris, Ani; Ahmed, Iqbal; Ho, Wan Jye (2007)

(untitled)
The objective of this research is to investigate the performance of blend cellulose acetate (CA)-polyethersulfone (PES) membranes prepared using microwave heating (MWH) technique and then compare it with blend CA-PES membranes prepared using conventional heating (CH) method using bovine serum albumin solution. The superior membranes were then used in the treatment of palm oil mill effluent (POME). Various blends of CA-PES have been blended with PES in the range of 1-5 wt %. This distinctive series of dope formulations of blend CA/PES and pure CA was prepared using N, N-dimethylformamide (DMF) as solvent. The dope solution was prepared by MW heating for five minutes at a high pulse and the membranes were prepared by phase inversion method. The performances of these membranes were evaluated in terms of pure water and permeate flux, percentage removal of total suspended solids (TSS), chemical oxygen demand (COD) and biochemical oxygen demand (BOD). Results indicate blend membranes prepared using the microwave technique is far more superior compared to that prepared using CH. Blend membranes with 19 % CA, 1-3 % PES and 80 % of DMF solvent were discovered to be the best membrane formulation.